2015
DOI: 10.1016/j.imbio.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Compstatin analog Cp40 inhibits complement dysregulation in vitro in C3 glomerulopathy

Abstract: C3 glomerulopathy (C3G) defines a group of untreatable ultra-rare renal diseases caused by uncontrolled activation of the alternative complement pathway. Nearly half of patients progress to end stage renal failure within 10 years. Cp40, a second-generation compstatin analog in clinical development, is a 14 amino-acid cyclic peptide that selectively inhibits complement activation in humans and non-human primates by binding to C3 and C3b. We hypothesized that by targeting C3 Cp40 would provide an effective treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…By binding to C3 and C3b, compstatin analogues prevent C3 opsonization by all initiation routes, thereby impairing amplification, downstream C5 activation, and effector generation. Among other indications 155 , the lead analogue Cp40 has shown efficacy in an in vitro model of C3 glomerulopathy 160 . Although systemic inhibition of C3 had been considered restrictive because of its high plasma concentration and turnover (BOX 3), a 2014 study demonstrated that target-saturating concentrations of Cp40 can be maintained in monkeys by repetitive subcutaneous injection 161 .…”
Section: Complement-targeted Therapymentioning
confidence: 99%
“…By binding to C3 and C3b, compstatin analogues prevent C3 opsonization by all initiation routes, thereby impairing amplification, downstream C5 activation, and effector generation. Among other indications 155 , the lead analogue Cp40 has shown efficacy in an in vitro model of C3 glomerulopathy 160 . Although systemic inhibition of C3 had been considered restrictive because of its high plasma concentration and turnover (BOX 3), a 2014 study demonstrated that target-saturating concentrations of Cp40 can be maintained in monkeys by repetitive subcutaneous injection 161 .…”
Section: Complement-targeted Therapymentioning
confidence: 99%
“…The percentage of PI-positive cells (compared to total cells) was used to evaluate the degree of cell death. The inhibition percentage was calculated as described elsewhere [7,21,22], using the following equation: % inhibition = {1 – (A – C) / (B – C)} × 100%, where A, B, and C represent the percentage of cell death when incubated with 20% serum pretreated with Cp40 (A), 20% serum without any treatment (B), and 20% heat-inactivated serum (C), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In a clinically relevant study on paroxysmal nocturnal hemoglobinuria (PNH), Cp40 was found to effectively protect PNH erythrocytes from both intravascular and extravascular hemolysis in vitro , thereby showing potential therapeutic advantage over the established anti-C5 therapy [5]. In another preclinical study, Cp40 was able to inhibit complement dysregulation in vitro in C3 glomerulopathy and may therefore offer a novel therapeutic option for affected patients [7]. In addition, Cp40 has been shown to be a potent inhibitor of complement activation in several in vivo and ex vivo animal models, such as a primate model of hemodialysis-induced complement activation [8], a ligature-induced periodontitis model in nonhuman primates (NHP) [9], and a xenogeneic model of interactions between human whole blood and porcine endothelium [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials utilizing targeted complement inhibition with novel agents are ongoing and may offer hope in treating these dreadful conditions. 21 …”
Section: C3 Glomerulopathiesmentioning
confidence: 99%